NATIONAL SECURITY OF THE REPUBLIC OF NORTH MACEDONIA AND ITS COHERENT IMPLEMENTATION OF NATIONAL INTERESTS (Security Dialogues, 2025)
National security is a segment that is considered from the perspective of an integralpart of the theory of regional security complex. The focus of this paper is to determinethe relevance of the state national interests, with special reference to giving appropriateproposals in the part of better management of them in the future and its more adequatecomplementarity during the renewal of strategies. The necessity of rebuilding the nationalinterests is necessary in order to monitor the fight against modern threats. The need tospecify long-term national interests is of vital importance for every modern state, so ourstate needs to build a solid foundation for the analogous functioning of all segments of thestate system by specifically defining strategic national interests based on the existing ones.Analogous to what was written, certain theoretical proposals were given that would be usefulin terms of the survival of national interests as the core of a state and a guide for furtherstrategic challenges.
Keywords: security, nation, interest